Proceedings of the International Dental Conference of Sumatera Utara 2017 (IDCSU 2017) 2018
DOI: 10.2991/idcsu-17.2018.69
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Treatment Needs Based on Aesthetic Component (AC) among Adolescents in Medan

Abstract: Abstract-The prevalence of malocclusion in Indonesia is high while dental health behaviour among adolescents especially towards malocclusion is inadequate whereas health services has not been satisfied. One of the most used index, Index of Orthodontic Treatment Need which consists of aesthetic component and dental health component. The aim of this research was to identify orthodontic treatment need based on aesthetic component among adolescents in Medan. This is a descriptive research with crosssectional desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The AC revealed a treatment need of 25% (moderate 24%, definite 1%) among our study participants. This is much higher than that assessed among Ethiopian children,[ 6 ] Indonesian adolescents (19.6%),[ 24 ] Spanish adolescents,[ 25 ] and Turkish adolescents,[ 26 ] but lower than 55.5% obtained in Indian adolescents. [ 27 ] Differences may be due to age of study populations as malocclusion has been shown to worsen with age,[ 28 ] as well as ethnic variations in perceptions of beauty.…”
Section: Discussionmentioning
confidence: 59%
“…The AC revealed a treatment need of 25% (moderate 24%, definite 1%) among our study participants. This is much higher than that assessed among Ethiopian children,[ 6 ] Indonesian adolescents (19.6%),[ 24 ] Spanish adolescents,[ 25 ] and Turkish adolescents,[ 26 ] but lower than 55.5% obtained in Indian adolescents. [ 27 ] Differences may be due to age of study populations as malocclusion has been shown to worsen with age,[ 28 ] as well as ethnic variations in perceptions of beauty.…”
Section: Discussionmentioning
confidence: 59%